Violation of The Law in The Case of Divorce Verstek - Muzakir, Muzakir; Yazid, Imam; Nurcahaya, Nurcahaya (Al-Daulah : Journal of Criminal Law and State Administration Law, 2023)
The research aims to answer the problem of legal violations in verstek divorce cases. This research is an empirical legal research with a qualitative approach, and data collection in this research uses observation, interview, and data analysis techniques. This research found that in verstek divorce cases, violations of the law can occur if there are violations of procedures or rights guaranteed by law in the divorce process. The following are some examples of legal violations that may occur in verstek divorce cases, namely violation of the rights of absent parties, non-compliance with procedural requirements, violation of the rights of absent parties in the decision, fraud or manipulation in the divorce process. Forms of violation of taklik talak which are used as reasons for filing for divorce, among others, leaving the wife for 2 consecutive years, not providing mandatory maintenance for 3 months, hurting the wife's body / body or, neglecting or not caring for the wife for 6 months or more. Keywords: Violations Law; Divorce; Verstek